2021
DOI: 10.3390/polym13244456
|View full text |Cite
|
Sign up to set email alerts
|

Copolymerization of Ethylene with Selected Vinyl Monomers Catalyzed by Group 4 Metal and Vanadium Complexes with Multidentate Ligands: A Short Review

Abstract: This paper gives a short overview of homogeneous post-metallocene catalysts based on group 4 metal and vanadium complexes bearing multidentate ligands. It summarizes the catalytic behavior of those catalysts in copolymerization of ethylene with 1-olefins, with styrenic monomers and with α,ω-alkenols. The review is focused on finding correlations between the structure of a complex, its catalyst activity and comonomer incorporation ability, as well as the microstructure of the copolymer chains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 99 publications
0
8
0
Order By: Relevance
“…To date, diverse vanadium(III, IV, V) complexes have been synthesized and evaluated in olefin polymerization (for example [9,14] ) and achievements in catalytic polymerization with the latest generation of vanadium catalysts are summarized in detail in the reviews. [1,13,15,16] Some representative vanadium(IV) complexes for ethylene polymerization are shown in Figure 1. [15] In 2019 Zanchin and co-workers developed several (imido)vanadium(IV) dichloride complexes, which catalyzed the polymerization of ethylene after the addition of Et 2 AlCl and ETA.…”
Section: Introductionmentioning
confidence: 99%
“…To date, diverse vanadium(III, IV, V) complexes have been synthesized and evaluated in olefin polymerization (for example [9,14] ) and achievements in catalytic polymerization with the latest generation of vanadium catalysts are summarized in detail in the reviews. [1,13,15,16] Some representative vanadium(IV) complexes for ethylene polymerization are shown in Figure 1. [15] In 2019 Zanchin and co-workers developed several (imido)vanadium(IV) dichloride complexes, which catalyzed the polymerization of ethylene after the addition of Et 2 AlCl and ETA.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3 partially lists several such precatalysts, which are usually Spaleck 17,19,[21][22][23] and constrained geometry types, 5,[24][25][26][27][28] tridentate titanium, 29,30 and tetradentate zirconium post-metallocenes, 29,31 and Nomura (cyclopentadienyl)(aryloxy)titanium post-metallocenes. 32 One F I G U R E 1 Copolymer morphology progression in a thermoplastic elastomer due to increasing comonomer incorporation.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3 partially lists several such precatalysts, which are usually Spaleck 17,19,21–23 and constrained geometry types, 5,24–28 tridentate titanium, 29,30 and tetradentate zirconium post‐metallocenes, 29,31 and Nomura (cyclopentadienyl)(aryloxy)titanium post‐metallocenes 32 . One can review the references listed above, including the corresponding cross‐references, for learning this subject in further detail.…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of some polar functionalized comonomers can efficiently alter the nonpolar nature of polyolefins and introduce new material properties [20–25] . The incorporation of a large content of α‐olefins can decrease crystallinity and enable elastic properties, leading to the generation of polyolefin elastomers (POEs) [26,27] . Interestingly, recent studies have shown that the elastic properties can also be installed through branching formation via chain walking homopolymerization of ethylene [28–32] .…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24][25] The incorporation of a large content of α-olefins can decrease crystallinity and enable elastic properties, leading to the generation of polyolefin elastomers (POEs). [26,27] Interestingly, recent studies have shown that the elastic properties can also be installed through branching formation via chain walking homopolymerization of ethylene. [28][29][30][31][32] The incorporation of cyclic comonomers such as norbornene endows cyclic olefin copolymers (COC) with unique properties such as high heat stability, good chemical resistance, low density and high transparency.…”
Section: Introductionmentioning
confidence: 99%